Physical impairments in Adults with Developmental Dysplasia of the Hip (DDH) undergoing Periacetabular osteotomy (PAO): A Systematic Review and Meta-Analysis - Michael J M O'Brien; Julie S Jacobsen; Adam I Semciw; Inger Mechlenburg; Lisa U Tønning; Chris J W Stewart; Joshua Heerey; Joanne L Kemp (International Journal of Sports Physical Therapy)
# Background